SNAKE VENOM ENZYMES NEUTRALIZATION POTENTIAL OF PHYTOCHEMICALS EXTRACTED FROM DATURA ALBA SEEDS - Syeda Maryam Fatima; Wajiha Tahir; Mahera Moin; Humera Waheed; Hanzala Khan (Journal of Animal and Plant Sciences, 2024)
Datura is a flowering perennial herb, belonging to the family Solanaceae, is widely distributed in many countries including Pakistan, and other tropical and sub-tropical parts of the world. The present study explored the bioactivities of phytochemicals obtained from Datura alba n-hexane and n-butanol seed extracts. The seed extracts showed the presence of flavonoids, terpenoids and alkaloids while saponins were absent. The n-hexane extract showed 100% human salivary amylase and 19% snake venom PLA2 (svPLA2) inhibition activity at examined lowest and highest concentrations respectively. It also exhibited mild (24% RSA) antioxidant activity at highest concentration (600 µg/µl) analyzed. On the other hand, salivary amylase inhibition and potent (80% RSA) antioxidant activity at 100 µg/µl concentration was observed in n-butanol extract. Interestingly, n-hexane extract showed snake venom protease while n-butanol extract showed svPLA2 enhancing activity and no venom anti-protease activity. The study demonstrated that both n-hexane and n-butanol extracts are natural sources of antioxidant and antidiabetic compounds. The n-hexane extract showed venom PLA2 neutralization which is reported for the first time.
Keywords: Traditional medicine; Datura alba; Anti-phospholipase A2; Anti-amylase; Antioxidant